Peningkatan Kesadaran Hukum Masyarakat Mengenai Sertifikasi Tanah Wakaf Guna Menjamin Kepastian Hukum di Desa Pentadu Barat Kecamatan Tilamuta. - Nirwan Junus; Mutia Cherawaty Thalib; Nurul Fazri Elfikri; Suwitno Yutye Imran; Dolot Alhasni Bakung (Jurnal Pelayanan Hubungan Masyarakat, 2023)
Waqf is a waqif legal act to separate and or give part of one's property to be used forever or for a certain period of time in accordance with the interests of worship and or general welfare according to sharia. In order to avoid disputes and problems related to waqf goods or land and to clarify their legal status, waqf goods must be registered and certified. Waqf Land Certification is the process by which the National Land Agency issues Waqf Land Certificates after Nazhir submits a Waqf Land Registration. Article 39 of Government Regulation Number 42 of 2006 concerning Implementation of Law Number 41 of 2004 concerning Waqf contains provisions concerning registration of land ownership certificates, and Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 2 of 2017 concerning Procedures for Land Registration Waqf at the Ministry of Agrarian Affairs and Spatial Planning. Related to the importance of the legitimacy of a land, it often triggers legal problems, namely that land owned by the community has not been registered as a result of a lack of understanding of the importance of waqf land certification. Taking into account the legal issues above, the Community Service Team at the Faculty of Law, State University of Gorontalo carried out this community service activity as an effort to increase Community Legal Awareness Regarding Waqf Land Certification to Guarantee Legal Certainty..